Trajectory of achievement in primary school and development of mental health conditions in adolescence: a cohort study using linked health and education data. (November 2016) - Rahman, Muhammad Azizur; Kerr, Mike; John, Ann; Potter, Robert; Kennedy, Jonathan; Brophy, Sinead
Abstract: Background: Little is known about how mental health in primary school affects subsequent adolescent mental health. This study examined the effect of education in primary school on development of mental health conditions. Methods: This cohort study of all children in Wales between 1999 and 2014 used routine data from general practice and hospital data linked with education records held in the Secure Anonymised Information Linkage (SAIL) databank. Cox regression was used, controlling for sex, deprivation, conduct disorder, attention deficit hyperactivity disorder, and learning difficulty. Findings: Health records of 652 903 children (319 839 boys, 307 584 girls) were linked with educational records: between the ages of 12 and 21 years, 33 498 children (5·1%) developed depression, 15 946 (2·4%) self-harmed, and 2183 (0·3%) had eating disorders. 10 458 boys (3·2%) and 23 040 girls (7·5%) had diagnosed depression during their childhood, and 10 550 boys (3·3%) and 21 278 girls (6·9%) were given an antidepressant. Children who developed depression were more likely than those not developing depression to have passed key stage 1 (age 7 years) (adjusted hazard ratio [HR] 1·19, 95% CI 1·08–1·30) but not key stage 2 (age 11) (0·76, 0·69–0·83), indicating that they were declining in primary school education. Conversely those who self-harmed (4736 boys [1·5%], 11 210 girls [3·6%]) were achieving as well as those who did not self-harm (1·02, 0·92–1·12). In children with an eating disorder, only female sex was associated with development of the disorder (10·5, 7·55–14·5), and educational achievement was not significantly different from those without the disorder (1·16, 0·82–1·63). However, at key stage 3 (age 14) children with eating disorders achieved well in secondary school (1·42, 1·2–1·7). Interpretation: The trajectory of achievement in primary school is very different for children who develop depression, self-harm, or eating disorders. Those who developed depression were deprived children declining in primary school education; those who self-harmed were deprived children improving in primary educational achievement. However, eating disorders were not associated with education or deprivation in primary school but associated with high achievement in secondary school. Funding: National Centre for Population Health and Wellbeing Research.